2012
DOI: 10.1111/j.1744-7909.2012.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Under‐ and Over‐supply Induces Distinct Protein Responses in Maize Xylem SapF

Abstract: Xylem sap primarily transports water and mineral nutrients such as nitrogen (N) from roots to shoots in vascular plants. However, it remains largely unknown how nitrogenous compounds, especially proteins in xylem sap, respond to N under‐ or over‐supply. We found that reducing N supply increased amino‐N percentage of total N in maize (Zea mays L.) xylem sap. Proteomic analysis showed that 23 proteins in the xylem sap of maize plants, including 12 newly identified ones, differentially accumulated in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
(99 reference statements)
1
12
0
Order By: Relevance
“…Under N deficiency, many N transporters and proteins mediating N metabolism have differential expression or accumulation (Yang et al 2011;Liao et al 2012a;Schlüter et al 2012;Garnett et al 2013), although no specific genes mediating N uptake and assimilation were identified with differential expression in rice seedlings at the early stage of N limitation (Lian et al 2006). Here, we found eight genes regulating N assimilation with significant down-regulation at the transcriptional level in the ZD958 root after 12-day N deficiency (Fig.…”
Section: Differential Regulation Of Genes Mediating N Transport and Mmentioning
confidence: 69%
See 1 more Smart Citation
“…Under N deficiency, many N transporters and proteins mediating N metabolism have differential expression or accumulation (Yang et al 2011;Liao et al 2012a;Schlüter et al 2012;Garnett et al 2013), although no specific genes mediating N uptake and assimilation were identified with differential expression in rice seedlings at the early stage of N limitation (Lian et al 2006). Here, we found eight genes regulating N assimilation with significant down-regulation at the transcriptional level in the ZD958 root after 12-day N deficiency (Fig.…”
Section: Differential Regulation Of Genes Mediating N Transport and Mmentioning
confidence: 69%
“…At the molecular level, N deficiency causes genome-wild changes in gene expression and carbon and N metabolism in arabidopsis (Bi et al 2007); however, genes regulating N uptake and assimilation showed no significant difference in N-deficient rice seedlings in contrast to quick changes in expression of genes mediating metabolism, protein synthesis, and transport facilitation (Lian et al 2006). In maize, N deficiency causes a series of changes in gene expression and protein accumulation directly affecting N uptake and metabolism, amino acid transport, and protein metabolism (Yang et al 2011;Liao et al 2012a;Schlüter et al 2012Schlüter et al , 2013Garnett et al 2013;Humbert et al 2013). However, little is known about how hybrid maize, especially dominant hybrids in the field, respond to N limitation at physiological and molecular levels, and whether they have similar or contrasting responses compared with inbred lines and wild maize?…”
Section: Introductionmentioning
confidence: 96%
“…Proteomic differences related to biotic and abiotic stress have been analyzed, such as in response to salicylic acid (Wu et al 2012), water deficit (Zhu et al 2007;Vincent et al 2005), infection (Campo et al 2004), and drought (Alvarez et al 2008). Recently, Liao et al (2012a) identified five N-related proteins in the xylem sap of maize, and in response to N availability changes in some proteins in the roots and leaves have been identified (Prinsi et al 2009). However, no information is available on proteins in the leaves and roots that are regulated by low N in seedlings of maize with different NUE.…”
Section: Xining Jin and Weihua LI Contributed Equally To This Workmentioning
confidence: 97%
“…To cope with N deficiency, plants have developed multiple levels of strategies to increase N acquisition and use efficiency, which have been well illustrated through physiological, genetic, and molecular studies [5,6,35,36]. Proteomic analysis of proteins responsive to short-and long-term N deficiency was also performed in plants, including maize, rice, Arabidopsis, triticale (Triticosecale wittmack), wheat (Triticum aestivum), barley (Hordeum vugare), tobacco (Nicotiana tabacum), and creeping bentgrass (Agrostis tolonifera) through 2-D, followed by MS analysis [37][38][39][40][41][42][43][44][45][46][47][48][49], which was briefly summarized (Fig. 2, Table 2).…”
Section: N Deficiencymentioning
confidence: 99%
“…symptoms of N deficiency were obviously observed) in leaves and roots ( Table 2). Results showed that most responsive proteins identified from leaves and roots were distinct, suggesting leaves and roots might exhibit different adaptive strategies to longterm N deficiency [37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: N Deficiencymentioning
confidence: 99%